Edukasi Pencegahan Stunting Dengan Metode Penyuluhan Di Puskesmas Sijamapolang Kabupaten Humbang Hasundutan - Lasria Simamora; Lumianna Simorangkir; Erny Syarifah Rajagukguk; Henny Rista; Deby Cintya Yun (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In the working area of ​​the Sijamapolang Community Health Center, Humbang Hasundutan Regency, stunting is still relatively common. Stunting is important to handle because it concerns the quality of human resources. Stunting, apart from being a risk of hampering physical growth and susceptibility to disease, also causes barriers to cognitive development which will affect the level of intelligence and productivity of children in the future. Stunting can be caused by various factors, including low nutritional intake in the first 1,000 days of life, from the fetus to a two-year-old baby. Apart from that, poor sanitation facilities, lack of access to clean water, and lack of environmental cleanliness are also causes of stunting. Poor hygiene conditions mean that the body has to fight extra hard against sources of disease, thus hampering the absorption of nutrients. Basically, stunting can be prevented from an early age. Of course, this can be done by increasing the family's insight or knowledge, especially mothers, regarding stunting prevention. By looking at the problems of these partners, the Community Partnership program aims to provide knowledge and information to the community so they can prevent and overcome the problem of stunting. The results achieved in this activity, namely, participants have knowledge about: the definition of stunting and its characteristics, the causes of stunting, the impacts of stunting, how to prevent and overcome stunting